Translation and Interpretation of Ella C. Deloria's "A Sioux Captive Rescued by his Wife" - Martin, Kathleen Jeanette (DigitalCommons@CalPoly, 1998)
In general, Native American communities provide a tradition of education for children based on oral narrative and storytelling. Oral narrative is indispensable in the understanding and maintenance of cultural traditions (Egan, 1987; Goody, 1995; Havelock, 1986) and displays cultural differences through language (Hymes, 1981) as well as providing the means for the continuation of community beliefs and traditions. Nora and Richard Dauenhauer (1990) note, Tlingit stories connect people and are "like a gaff hook reaching out across a distance and becoming hooked with another person who is hooked" (p. ix). Jerome Bruner (1986) identifies narrative as a way to put "timeless miracles into the particulars of experience, and to locate the experience in time and place" (p.13). Narratives and stories engage others in multi-layered experience and provide the opportunity to bridge differences between peoples. The transcription, translation and interpretation of Native oral literatures has not always provided fair and accurate representations of the multiple meanings and teachings present in the texts. "The apparent lack of literary value in many past translations is not a reflection but a distortion of the originals, caused by the diction process, an emphasis on content, [and) a pervasive deafness to oral qualities" (Tedlock, 1983b, p. 74). Substantial contributions to the field can be found, however, in the work of Dennis and Barbara Tedlock, (1983), Brian Swann (1992), Dell Hymes (1981), and recently, Julian Rice (1994). For the most part, however, the translation and interpretation of traditional narratives has not been pursued or utilized as a form of literature (Swann, 1992; Rice, 1994). In addition, the direct implications of stories and narratives with regard to traditional ideals and values have been, only in a few instances, based on sociolinguistic and cultural perspectives. This paper presents a free translation, analysis, and interpretation of "A Sioux Captive Rescued by his Wife" (Rice, 1994), a Lakota narrative ...